Supernormal Stimulus Begging Calls of Brood‐Parasitic Nestlings Depress the Parental Care in an Uncommon Host - Li Tian; Ruiying Han; Jingyi Su; Shuting Jia; Cuiping Yi; Jieru Wen; Zhengwang Zhang; Donglai Li; Yu Liu (Ecology and Evolution, 2025)
ABSTRACT During the nestling period, brood‐parasitic birds stimulate host parents to provide food through complex visual and auditory signals, including emitting supernormal stimuli in the form of begging calls to increase the feeding frequency. However, whether the begging calls of brood‐parasitic nestlings act as a universal type of supernormal stimulus signal and their effects on less common host species still require further research. In this study, we used playback recordings to verify the impact of the begging calls of Common Cuckoo (Cuculus canorus) nestlings on the parental care behavior of host Barn Swallow (Hirundo rustica) parents. Contrary to our expectations, the results showed that male Barn Swallow parents decreased their feeding frequency in response to both types of Common Cuckoo nestling calls (cuckoo nestlings reared by the Oriental Reed Warbler Acrocephalus orientalis/the Barn Swallow), while females decreased their feeding frequency in response to the begging calls of Common Cuckoo nestlings reared by the common host (the Oriental Reed Warbler). Additionally, brood size, temperature, and weather all affected the feeding frequency in the Barn Swallow. This study supports the idea that the supernormal stimulus of brood‐parasitic nestling begging calls does not always work as a universal signal; the behavioral adaptations formed by parasitic birds in response to common hosts may lead to reduced fitness when utilizing uncommon hosts, for example, the Barn Swallow.